Deconstruction of the principal constitutional guarantees regarding the social security of informal laborers in Colombia - Moreno Villamizar, Manuel Mauricio (DIXI, 2020)
Objectives: The objective of this article is to link the principled trilemmatic nature of the efficiency, solidarity and universality of the comprehensive social security system in the face of informality in the Colombian territory, which ignores the minimum constitutional and legal guarantees provided by the Social State of Law in the defense and protection of rights inherent to the human condition. Social security has a fundamental character in the Social State of Law that contrasts with reality and, specifically, in the labor and social security context of the informal sector. Informality in Colombia is a reflection of social injustice and inequality as a consequence of the phenomenon of globalization and labor flexibility that leads to increasing job insecurity, since the State restricts and limits rights with some characteristics of public policy of exclusion, primacy of the neoliberal economic model and prevailing legalism. Methodology: The applied research model is chosen as a research reference when it is correlated with other disciplines of knowledge and realities that are articulated with the social sciences. A legal philosophical approach is assumed that seeks the analysis of legal norms, their correspondence or discrepancy in the face of the set of values and principles of society, by determining the relationship between law and justice as the central axis of the investigation. Conclusion: Informality needs to be analyzed, reconstructed and interpreted from the philosophy of law by redefining labor law and social security as inherent rights of man.